The diagnosis of the technical-tactical preparation of judo competitors during the World Championships (2009 and 2010) in the light of the new judo sport rules - Adam, M.; Smaruj, M.; Tyszkowski, S. (Archives of Budo, 2011)
Background: Very important changes in judo sport combat regulations were introduced in 2009-2010. The purpose of those changes was to make judo combat more attractive and to eliminate or reduce the techniques which do not derive from the accepted classification of judo techniques (grasping opponent`s legs). The aim of our research was to determine the impact of the new judo rules on the effectiveness of techniques and the results achieved by men`s national judo teams.